Is this being a psychologist? Reflections on the construction of the professional role in sports fields (Impetus, 2023)
The present work exposes some experiences of the work in psychology within the framework of the construction of the professional role in sports environments. From the dialogue with the materials of the situated practice of accompaniment, assistance and psychological orientation, some situations are analyzed from the possibilities and limits that we find when we start the professional exercise. Focusing on the discussion between the theoretical baggage and the concrete practices, this article aims to contribute to the reflection the potential of implication analysis as a key process in the construction of your role in the field.
Keywords: psychology; sports; intervention; professional role